POTENTIAL OF RAINWATER HARVESTING IN BUILDINGS TO REDUCE OVER EXTRACTION OF GROUNDWATER IN URBAN AREAS OF BANGLADESH - Dakua, Maharam; Akhter, Fahmida; Biswas, Partha Protim; Siddique, Md. Latifur Rahman; Shihab, Reyad Morshed (European Scientific Journal, ESJ, 2014)
Rainwater harvesting is an ancient technique which is very simple. In countries like Bangladesh, where annual rainfall is high, rainwater could meet a significant amount of total demand. Due to maladaptation to the paradigm of extraction of groundwater without considering the sustainability, people in Dhaka and other urban areas in Bangladesh are still reluctant to use this abundant source. This paradigm has been pushing the water supply scenario of Dhaka city closer to a condition where the city might face permanent water crisis, once the underground aquifers goes down below the pumping level or the aquifers become dry. Also the surface water condition of peripheral rivers of Dhaka city is in poor condition which does not encourage increasing use of surface water in Dhaka city. As an alternative of these options, rainwater harvesting has been considered though majority of the users are not fully aware of its potential to become a source of water. Analysis of the catchment availability and size of storage tanks are needed to find the potential of rainwater harvesting in the building and the capacity of buildings to store rainwater and use it. In this paper, an attempt was made to calculate the potential of rainwater harvesting in large and small premises of Dhaka city. Also the possible financial benefit from rainwater harvesting was also analyzed in this paper which would bring interest of the users.